Analysis And Strategy Increasing of Traditional Fisherman Exchange Rate in The Situbondo District - Ramli; Ulfatul Mardiyah; Moh. Rasidi; Yona Wahyu Lolita (Proceeding International Conference on Religion, Science and Education, 2023)
One indicator that is believed to be used to see the welfare of fishermen households is the fisherman exchange rate. The purpose of this research is to analyze and formulate a strategy to increase for traditional fishermen exchange rate in The Situbondo District. The method used to measure fishermen exchange rate is a survey and to formulate a strategy to increase fishermen exchange rate is SWOT (Strength-Weaknesses-Opportunities-Threats) and QSPM (Quantitative Strategic Planning Matriks). The results of this study indicate that the traditional fishermen exchange rate for in 2022 in The Situbondo District is 1.05. The strategy to increase the traditional fisherman exchange rate based on the priority scale is 1) empowering fishermen based on increasing productivity and improving lifestyles, 2) improve the trading system of fish catches in favor of fishermen, 3) improve skills and competencies of fishermen in techniques and management of fishing to achieve effectiveness and efficiency, 4) increasing fish catches through modernizing boats and catching tool that are environmentally friendly, 5) developing an application to read the weather and fishing ground based on android, 6) forming productive economic business groups as an effort to get additional income outside of fishing activities, 7) increasing access to capital for productive businesses through the revitalization of fishermen cooperatives dan 8) provide easy credit with low interest.